Corporate governance and nested entrepreneurial team performance: An entrepreneurial process governance system - Lim, Teck Ting (2017)
Academically, this research study helps to close some of the research gaps on entrepreneurship and corporate governance. In the entrepreneurial perspective, it provides a paradigm shift in viewing entrepreneurship as a body of knowledge, an extension of Timmons’ model of entrepreneurial process and the mechanisms of both entrepreneurial and nested entrepreneurial processes. On the corporate governance perspective, it commences the practical views of implications of governing the nested entrepreneurial team processes. The disciplinary and cognitive levers of Charreaux’s Meta model of governance were used to guide the design considerations of Process Governance System (PGS) as the change agent for providing the dual outcomes of research and actions. The practical nature of the research concerns how SMM uses corporate governance in overcoming specific challenges it faced for maximizing long term entrepreneurial values creation under situation of high growth. The theoretical concerns of the research could be viewed as an attempts of moving nested entrepreneurial team governance research from literature-driven approach to a real practical scenario and exploring the influence of governance system, in the absence of venture capitalists interference, on the endogenous growth of nested entrepreneurial team. Analysis on the outcomes of interventions by PGS shows that both the cognitive and disciplinary levers of PGS are complimentary to each other in mechanizing the six supportive social-economic structures underpinning the three nested entrepreneurial processes.